Guidance and Counseling Strategies on Handling Student Discipline at a Religious-Based Junior High School in Gowa District, Indonesia - Sari, Citra Dewi Indra; Suwandayani, Beti Istanti; Waluyo, Lud (The Indonesian Institute of Science and Technology Research, 2025)
This study aims to identify the guidance and counseling strategies used to address student discipline issues at MTs Muhammadiyah Lempangang, Gowa Regency; and the effectiveness of these strategies in managing student discipline. This research employed a qualitative approach supported by descriptive data. Data collection techniques included observation, interviews, and document analysis. Data analysis was carried out using the qualitative interactive research model, which includes data reduction, data display, and conclusion drawing. The preparatory phase of the guidance and counseling strategy includes identifying problems, developing instruments, scheduling, and direct observation. These activities were implemented through routine programs and classroom management efforts. The implementation of guidance and counseling strategies was assessed through observation and interviews, supported by a decline in disciplinary violations, positive student responses, and the involvement of parents and teachers in the mentoring process. Based on research findings, it can be concluded that the guidance and counseling strategies for managing student discipline have been executed effectively and yielded positive results.